Carbon emission monitoring based on internet of things with cloud-tube-edge-end structure - Fangyuan XING; Shibo HE; Mingyang SUN; Jiming CHEN (物联网学报)
In recent years, China has participated in the global climate governance with a positive stance.The accurate, rapid, and reliable monitoring is fundamental for the situation awareness and layout optimization of the carbon emission.However, the state-of-the-art review with systematic studies of this topic has hardly been identified.The development process and the existing standards of carbon emission monitoring were investigated.The terminal equipment-based methods and the internet of things (IoT)-based applications for carbon emission monitoring were explored, and the IoT-based methods were concluded which hold the advantages including clear structure, flexible design, and reliable transmission.Based on the IoT, an industrial carbon emission monitoring method using the “cloud-tube-edge-end” IoT structure was established.The enabling technologies that can implement the functions of the “cloud-tube-edge-end” were summarized, which are expected to provide guidance for future carbon emission monitoring.